To Broadway - Mazars, Maurane (Abrams ComicArts, 2025)
"In this moving graphic novel, Maurane Mazars deftly illustrates an emotionally resonant character study of a young gay man struggling to express himself in the wake of World War II. Germany, April 1957. Uli is a modern dance student at the prestigious Folkwang University of the Arts who will do anything to pursue his dream of becoming a famous Broadway dancer. But Uli's dream and his energetic, outgoing personality hardly fit the melancholy culture of postwar Europe. During a fateful trip to Berlin, Uli meets Anthony, a young American dancer. The attraction is immediate, and Anthony convinces Uli to move to New York to try his luck on Broadway. The young men part ways, and Uli is inspired to pack his bags and embark on an adventure. Will Uli be able to seize his dreams in New York City? Or is he just one of the many young artists doomed to find a disappointing reality check in the Big Apple?" --